Effect of graphene oxide content on the tensile properties and swelling ratio of chitosan/xanthan gum/graphene oxide hydrogel films. (23rd July 2020) - Kim, Dong-Won; Shchipunov, Yury; Kim, Gue-Hyun; Shin, Inho; Ha, Chang-Sik
Abstract: In this study, chitosan (CS)/xanthan gum (XA)/graphene oxide (GO) nanocomposite hydrogels were prepared to enhance mechanical properties of CS/XA hydrogels. The hydrogels were characterized by Fourier-transform infrared spectroscopy (FT-IR) spectra, wide-angle X-ray diffraction (WXAD) patterns, thermogravimetric analysis, and universal testing machine. The swelling ratio of dried CS/XA and CS/XA/GO films were also measured in deionized water at 37 °C. The effect of GO content on the tensile properties and swelling ratio of CS/XA/GO hydrogel films were investigated. With addition of GO, tensile strength and modulus of CS/XA hydrogel films were improved without significant decrease of elongation at break, while the swelling ratio of CS/XA/GO films decreased with increasing GO contents.